The Role of Islamic Religious Education Teachers in Developing Islamic Values for Deaf Students at SLB - Andi Dzakiyatul Aliyah; Irsyad Alfath (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the faith, piety, and morals of students, including deaf students. However, the limitations of communication and the dominance of verbal methods in PAI learning are often obstacles in the process of internalizing Islamic values. This study aims to analyze the role of PAI teachers in developing Islamic values in deaf students at SLB Islam Qothrunnada Yogyakarta. This study uses a qualitative approach with a case study design. The research subjects included PAI teachers, principals, and deaf students who were selected purposively. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model by triangulating sources and methods. The results of the study show that PAI teachers play the role of educators, guides, role models, and facilitators of adaptive learning through example, worship habits, use of visual media, direct practice, positive reinforcement, and evaluations based on observation of religious behavior. This role is effective in helping deaf students understand and practice Islamic values contextually.